“Essay on Ci” by Li Qingzhao - Dashchenko, Anna (Respectus Philologicus, 2016)
The article presents the first Russian translation of “Essay on Ci” with detailed comments. It was written by the outstanding Chinese poetess Li Qingzhao and considered to be the first theoretical treatise dedicated to genre ci. The article revealed that the poetess used three strategies to make a genre demarcation: to legitimise, dichotomise and historicise. To legitimise means to justify that ci is a genre of poetry by identifying the same traits with official poetry shi (e.g. using the classical quotations and allusions). To dichotomise is to determine a core element of genre and oppose it to the other element identifying the similar genre (e.g. music separates ci from shi). To historicise is to develop or discover the unique historical past (e.g. the source of ci is in antiquity). The article also examined the strategy to invent classics: Li Qingzhao wrote the apophatic history of genre ci pointing not to the merits but weaknesses of her predecessors.
Keywords: Li Qingzhao; “Essay on Ci”; the Song dynasty; genre ci